1975
DOI: 10.1007/bf01469685
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glycosphingolipids in diabetics and normals

Abstract: In diabetic patients with hyperlipoproteinemia type IV the monohexosyl ceramide concentration in blood plasma is significantly elevated. This augmentation can be attributed to an increased monohexosyl ceramide content of the BLDL plasma fraction. In contrast, the di-, tri-, the tetrahexosyl ceramide levels remain within normal limits. In normolipidemic diabetics of comparable age, sex, and weight classes and of comparable metabolic control no elevations of glycolipid fractions could be found. However, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…In humans, there is an inverse correlation between metabolic disease and serum ceramides 90, 91 . In rodent models, ceramide accumulation is correlated with toxicity that leads to metabolic diseases, in particular the promotion of insulin resistance 92 .…”
Section: Role Of Intestinal Fxr In the Regulation Ceramidesmentioning
confidence: 99%
“…In humans, there is an inverse correlation between metabolic disease and serum ceramides 90, 91 . In rodent models, ceramide accumulation is correlated with toxicity that leads to metabolic diseases, in particular the promotion of insulin resistance 92 .…”
Section: Role Of Intestinal Fxr In the Regulation Ceramidesmentioning
confidence: 99%
“…Increased levels of sphingolipids such as glycosphingolipids (70), ceramide (71, 72), sphingosine (73), and sphinganine (72, 73) have been described in the plasma of patients with diabetes. More recently, it has become clear that the intracellular sphingolipid composition in podocytes and other cells of the kidney glomerulus may contribute to the pathogenesis and progression of the disease (Table 1).…”
Section: Sphingolipid Accumulation In Glomerular Disease Of Non-genetmentioning
confidence: 99%
“…It has long been appreciated that sphingolipid levels are perturbed in the blood plasma of diabetic patients. The first such finding indicated that glycosphingolipids were elevated in the plasma of some groups of diabetic human patients (Kremer et al 1975). This was later confirmed by a study demonstrating that glucosylceramide was elevated in the plasma of diabetics (Serlie et al 2007).…”
Section: Sphingolipids As Biomarkers Of Diabetesmentioning
confidence: 99%